PRA PENUNTUTAN DAN PENUNTUTAN - Maimuna, Siti; Karim, Moh (LPPM Universitas Bina Bangsa, 2025)
This research aims to understand problems regarding pre-prosecution and prosecution as well as problems regarding the authorities in pre-prosecution and prosecution and the authority of the public prosecutor. Pre-prosecution and prosecution are two important stages in the criminal justice process which determine the smoothness of a court proceeding to achieve peace and a decision from the court. Pre-prosecution is the initial stage carried out before carrying out a prosecution by an investigator. After the investigation is complete, the investigator gives the case files to the public prosecutor to re-examine the case submitted. The prosecution stage is where the public prosecutor submits the case to court after carrying out an examination which is declared complete and at this stage the public prosecutor draws up an indictment against the suspect based on the evidence that has been submitted by the prosecutor.